Cybertrance Devices: Countercultures of the Cybernetic Man-Machine. - Triclot, Mathieu (Substance: A Review of Theory & Literary Criticism, 2018)
This article examines a collection of "cybertrance" devices, originating in the 1960s and 1970s. These devices are based on the reappropriation of instruments from the academic world in order to place users in modified states of consciousness. They draw on the heritage of American cybernetics, and its mechanical philosophy, in order to explore what is machinelike in man. Their goal is to create unprecedented forms of experience by coupling body and machine, disturbing one by the other. The analysis focuses on the trajectories of objects, the circulation between theoretical elements from cybernetics and their technological reinterpretation in countercultural circles. Four ranges of devices are examined: the immersive multimedia installations of psychedelic culture, the flicker and its physiological effects, biofeedback devices, and the digital translations, in the world of computing, of these first analogical devices.